2015 3rd International Conference on Future Internet of Things and Cloud 2015
DOI: 10.1109/ficloud.2015.96
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and Predicting End-to-End Quality in Wireless Community Networks

Abstract: Abstract-Community networks are an emergent model with mottos like "a free net for everyone is possible" or "don't buy the network, be the network". Their social impact is measurable, as the community is provided with the right and opportunity of communication. The combination of wired and wireless links in these networks, and the unreliable nature of the wireless medium, poses several challenges to the routing protocol. End-toEnd quality tracking helps the routing layer to select paths that maximize the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…Moreover, the EtEQ prediction accuracy is analyzed some steps ahead in the future and also its dependency of the time of the day. In this work, we extend our previous work [19] but including several new analysis which would allow a better understanding of End-to-End quality prediction in Wireless Mesh Community Networks. Particularly, we provide: (1) a detailed analysis of path properties behavior showing that Path Quality prediction is possible and meaningful; (2) an analysis of the computational cost of the prediction in terms of CPU utilization, energy consumption and temperature to confirm that the prediction can be executed directly in the routers; and (3) a detailed analysis of an use case that shows the behavior of two orthogonal routing strategies, in terms of Packet Delivery Ratio, ETX of links, and End-to-End Delay.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the EtEQ prediction accuracy is analyzed some steps ahead in the future and also its dependency of the time of the day. In this work, we extend our previous work [19] but including several new analysis which would allow a better understanding of End-to-End quality prediction in Wireless Mesh Community Networks. Particularly, we provide: (1) a detailed analysis of path properties behavior showing that Path Quality prediction is possible and meaningful; (2) an analysis of the computational cost of the prediction in terms of CPU utilization, energy consumption and temperature to confirm that the prediction can be executed directly in the routers; and (3) a detailed analysis of an use case that shows the behavior of two orthogonal routing strategies, in terms of Packet Delivery Ratio, ETX of links, and End-to-End Delay.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 91%
“…Finally, Millán et al [19] focused on End-to-End quality prediction by means of time-series analysis. This prediction technique is applied in the routing layer of large scale, distributed, and decentralized networks.…”
Section: Link and End-to-end Quality Prediction In Heterogeneous Netwmentioning
confidence: 99%
“…As an example, the inter-download times of video segments are predicted in [102], where the output sequences are the interdownload times of the already downloaded segments and the states are the instants of the next download request. ARIMA: [13], [38], [40], [46], [47], [54], [58], [59], [63], [100], [119] Kalman: [32], [ CF: [16], [134], [149] Cluster: [15], [34], [51], [117], [122], [123], [148], [156] Decision trees: [35], [98], [ Functional: [28], [29], [38], [64], [99], [104], [105] SVM: [51], [114], [139] ANN: [14], [48], [106], [ 2) Bayesian inference: This approach allows to make statements about what is unknown, by conditioning on what is known. Bayesian prediction can be summarized in the following steps: 1) define a model that expresses qualitative aspects of our knowledge but has unknown parameters, 2) specify a prior probability distribution for the unknown parameters, 3) compute the posterior probability distribution for the parameters, given the observed data, and 4) make predictions by averaging ove...…”
Section: Statistical Methods For Probabilistic Forecastingmentioning
confidence: 99%
“…Recently, time-series analysis has been considered to estimate link quality (LQ) and end-to-end quality (EtEQ) in the routing layer, involving real-world wireless mesh community networks. For instance, Millan et al [19][20][21][22] shown that time-series analysis can be used to improve the performance of the routing protocol, by providing information that allows making appropriate and timely decisions. This contributes to maximize the message delivery rate and minimize traffic congestion at both levels (i.e., LQ and EtEQ) with a small average mean absolute error.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of predictors increases the complexity of the routing protocols, because of the additional hardware and software required to make and validate predictions. Moreover, penalty mechanisms are usually introduced to the system when there is a high rate of mispredictions, which negatively affect the performance of these protocols.Prediction mechanisms have been embedded in routing protocols to foresee several aspects of a network, such as nodes mobility [13], reliability of its topology [14,15] and quality of links and end-to-end paths [16][17][18][19][20][21][22][23][24]. These mechanisms have also been used to reach particular communication…”
mentioning
confidence: 99%